Outsourcing of unionized firms and the impacts of labour market policy reforms / - Erkki Koskela; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper shows that outsourcing of parts of the workforce in unionized firms leads to wage moderation and as long as the share of the outsourced workforce is not too large, this wage-moderation effect on domestic employment outweighs the direct substitution effect so that domestic employment increases in unionized firms as outsourcing costs fall. This does not affect the well-established qualitative results of the impact labour tax reforms have: changes in the wage tax rate, the tax exemption and the unemployment benefit payments affect domestic wage setting in the same way as in the absence of outsourcing. Furthermore, increasing the degree of tax progression by keeping the relative tax burden per worker constant continues to be good for employment. However, except for low outsourcing activities, the impact of these policy measures will become smaller as outsourcing costs fall.
Keywords: J41; J51; H22; 330; outsourcing : union wage-setting; employment; labour tax reform; Arbeitsmarkt; Outsourcing; Lohnniveau; Beschäftigungseffekt; Gewerkschaftlicher Organisationsgrad; Lohnsteuer; Steuerreform; Theorie